A pathway to microstructural refinement through double pulsed gas metal arc welding. (June 2017) - Wang, L.L.; Wei, H.L.; Xue, J.X.; DebRoy, T.
Abstract: In fusion welding, variations of cooling rate and microstructure are commonly achieved by changing heat input. Here we show that the cooling rates can be adjusted and microstructural features could be refined at constant heat input while changing the pulsing parameters. The temporal variations of cooling rates, solidification growth rate and weld geometry during both single and double pulsed welding of an aluminum alloy are examined. Furthermore, microstructures of both single and double pulsed gas metal arc welding are presented to demonstrate significant microstructural refinement of double pulsed gas metal arc welds for the same heat input. Graphical abstract: